AVA (AKASA VANA ASTHANA): INOVASI HUTAN PANGGUNG UNTUK PEMBANGUNAN BERKELANJUTAN YANG MENYOKONG KESEJAHTERAAN HIDUP MANUSIA DAN KELESTARIAN LINGKUNGAN HIDUP - Pamungkas, Nugroho Rinadi; Hariadhi, Eka Ramadhan; Ibrani, Prihantari Mukti; Kartjito, Maria Veronika; Maramis, Frenty Yohana Laurencya (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Sustainable development is development activities that can be ongoing and aimed at improving the quality of human life without life support beyond the ability of the ecosystem. But activities such as forest conversion to plantations, transmigration settlements, mining and logging, as well as forest concession are less responsible, contrary to sustainable development. In addition, the development in the big cities in Indonesia seems to ignore the environmental aspects and has caused ecological problems and social. Forest Concept Stage AVA (Akasa Vana Asthana) is the answer to the challenge of sustainable development by providing new forest land as a replacement or an addition to the already deforested forest area, without constrained by limited land significantly. This concept is preferred to be applied in urban areas, as it aims to bring back the forest functions and additional functions attached to them to address ecological problems in urban areas. Our idea is to make the forest above the city areas which will result in the preservation of the environment and impact on human welfare with the example is the landscape in the area of Surabaya. However, it is possible to apply this concept in other major cities in Indonesia.